2014
DOI: 10.1177/0267659114536456
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the perfusion system by integration of the components. Does it affect the hematocrit drop and transfused red blood cells? A retrospective audit

Abstract: Minimizing our CPB circuit by using integrated components has affected the drop of Hct and the amount of transfused RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A body of evidence suggests a reduction in prime volume is useful adjunct for minimizing RBC transfusion (8)(9)(10)(11). In addition, the STS', Society of Cardiovascular Anesthesiologists, and the International Consortium for Evidence-Based Perfusion recommend minimizing prime volume as an integral, evidence-based (Class I, Level A) blood conservation practice (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A body of evidence suggests a reduction in prime volume is useful adjunct for minimizing RBC transfusion (8)(9)(10)(11). In addition, the STS', Society of Cardiovascular Anesthesiologists, and the International Consortium for Evidence-Based Perfusion recommend minimizing prime volume as an integral, evidence-based (Class I, Level A) blood conservation practice (4).…”
Section: Discussionmentioning
confidence: 99%
“…The current Society of Thoracic Surgeon (STS) blood conservation guidelines recommend minimizing CPB circuit prime volume as an integral evidenced-based (Class I, Level A) strategy to reduce blood transfusions by decreasing hemodilutional anemia. In part related to these guidelines, a number of studies have been published (8)(9)(10)(11) documenting institutional efforts, focusing on reducing CPB circuit prime volumes. Previous studies (8)(9)(10)(11) have demonstrated that reducing the size of the CPB circuit and related prime volume may help to minimize hemodilution and subsequent RBC transfusions.…”
mentioning
confidence: 99%
See 1 more Smart Citation